The performance of quality controls in the Investigator® Quantiplex® Pro RGQ and Investigator® 24plex STR kits with a variety of forensic samples. (November 2021) - Harrel, Michelle; Mayes, Carrie; Houston, Rachel; Holmes, Amy S.; Gutierrez, Ryan; Hughes, Sheree
Abstract: Forensic DNA laboratories process database reference samples on FTA® cards or buccal swabs, which commonly contain adequate amounts of quality DNA resulting in full STR profiles and high first-pass rates. However, some reference samples and many forensic casework samples are exposed to a variety of insults that may lead to low quantities of DNA, DNA degradation, DNA mixtures, and/or PCR inhibition, posing a challenge to downstream genotyping success. The inclusion of multiple amplification targets and internal PCR controls (IPCs) in DNA quantification kits, and quality sensors within STR amplification kits can aid in the accurate interpretation of sample/profile quality, and guide more efficient rework strategies when needed. In order to assess the effectiveness of these quality systems we subjected database-type samples (buccal swabs and blood or saliva on FTA® cards), mock casework samples (low-template, degraded, inhibited, DNA mixtures), and authentic post-coital samples to various challenging conditions. Concordance between the quality flags in the Investigator® Quantiplex® Pro RGQ kit (QIAGEN), the QS markers in QIAGEN's Investigator® 24plex QS kit, and overall STR profile quality was evaluated for all casework-type samples. To assess the value of the QS markers in the Investigator® 24plex QS and GO! STR kits, samples with partial or failed STR profiles were reworked based on the quality of the electropherogram first with the QS markers redacted, and second in conjunction with the QS markers. Results from each of the rework approaches were compared to determine which strategy, if any, improved the STR profile quality and the number of reportable alleles. The QS markers in the 24plex STR kits correctly confirmed sample quality in 99.9% of databasing samples and 98% of mock casework samples. Quality flags during DNA quantification were concordant with downstream STR profiles for the majority (77%) of the mock casework samples. Additionally, when samples with partial STR profiles were reworked, more loci were obtained for 80% of the samples regardless of the rework strategy used. However, the most notable improvement in STR completeness was observed in inhibited samples that were reworked based on the information provided by the STR quality sensors, with an average increase of 56% reportable alleles. Highlights: QS markers correctly assessed > 98% of database and mock casework samples. QS markers aided interpretation of poor EPGs when sample quality was unknown. Quantiplex Pro RGQ predicted downstream profile quality in > 75% casework samples. Samples reworked using quality controls showed improvement in allele recovery. The quality marker systems were most beneficial in confirming DNA degradation.